2023
DOI: 10.1186/s10194-023-01671-5
|View full text |Cite
|
Sign up to set email alerts
|

European Headache Federation (EHF) critical reappraisal and meta-analysis of oral drugs in migraine prevention – part 3: topiramate

Bianca Raffaelli,
David García-Azorín,
Deirdre M. Boucherie
et al.

Abstract: Objective Topiramate is a repurposed first-line treatment for migraine prophylaxis. The aim of this systematic review and meta-analysis is to critically re-appraise the existing evidence supporting the efficacy and tolerability of topiramate. Methods A systematic search in MEDLINE, EMBASE, Cochrane CENTRAL, and ClinicalTrials.gov was performed for trials of pharmacological treatment in migraine prophylaxis as of August 13, 2022, following the Prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The proportion of patients who reported at least one TEAE was 35%, which is between that observed in the first RCT (46%) (8) and the second RCT (30%) (9). In addition, the tolerability profile was quite unique and not that different from that observed in the more novel preventive drugs (23). The most frequently reported AEs in this study were dizziness and tiredness, as expected, which are probably related to decreased blood pressure.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The proportion of patients who reported at least one TEAE was 35%, which is between that observed in the first RCT (46%) (8) and the second RCT (30%) (9). In addition, the tolerability profile was quite unique and not that different from that observed in the more novel preventive drugs (23). The most frequently reported AEs in this study were dizziness and tiredness, as expected, which are probably related to decreased blood pressure.…”
Section: Discussionsupporting
confidence: 64%
“…This is the first study to calculate 30% and 100% responder rates, and the analysis used two different approaches, including only patients who maintained candesartan (PP), and the entire study sample (ITT). In the most conservative assessment (ITT analysis and BCF imputation method for the missing data), the proportion of patients who achieved at least a 30% responder rate was 50% at the third month (weeks 8-12) and 49% at the sixth month (weeks [20][21][22][23][24]. This shows realistic and transparent results, which are not that different from those observed in other "old" oral preventive drugs, such as amitriptyline (20), flunarizine (21), and topiramate (22), where the absolute difference of patients who achieved a 50% response rate in monthly migraine days, compared to placebo, was 16.5% higher following amitriptyline and 16.8% higher following topiramate.…”
Section: Discussionmentioning
confidence: 99%
“…The anticonvulsant topiramate showed an upward trend in prescribing and drug expenditures. Several high-quality studies have shown that topiramate is an effective preventive medicine for migraine [ 25 , 26 ]. Limited data from comparative trials suggest that topiramate may have a modest advantage over valproate for episodic migraine prevention [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there was a moderate weight loss and improved glycated hemoglobin levels in T2D patients, a low dose of topiramate treatment had no significant effect on insulin sensitivity in obese females without established diabetes [ 149 ]. Topiramate seems to exhibit insulin secretagogue and sensitizing properties, however, the implications for its therapeutic use necessitate further investigation and consideration of potential severe side effects [ 150 ]. No evidence was found for a change in the pharmacokinetics of topiramate with concomitant insulin use.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Some antimigraine drugs are associated with weight loss, which may influence the activity of migraines, for instance topiramate, through modulation of GABA receptors [ 5 ]. Moreover, topiramate seems to exhibit insulin secretagogue and sensitizing properties, however, the implications for its therapeutic needs further investigation, considering its potential severe (congenital) side effects [ 61 , 150 ]. In addition, triptans may influence insulin, glucose metabolism and regulation of appetite, resulting in weight loss and potentially impacting glucose metabolism [ 41 , 42 ].…”
Section: Future Implicationsmentioning
confidence: 99%